The Influence of Politics, Existing Regulations and Knowledge on Street Vendors’ Perception on the Legal Status of Street Vending - Kirumirah, Mubarack Hamidu; Kayunze, Kim; Ringo, Justin (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In the absence of a comprehensive policy regarding the operations of street vending, the presence of contradicting regulations and stances between politicians and government officials on the legal status of vendors, it has been easy for vendors to build various perceptions regarding their legality which at last have led them to clash with urban authorities. For this paper, the researchers determined the influence of politics, existing regulations and vendors’ knowledge vendors’ perception on the legality of street vending operations in Dar es Salaam and Mwanza Cities, Tanzania. The paper is based on a study in which a quantitative approach with a cross-sectional survey design was used to collect data from 371 respondents who were selected using proportionate stratified sampling. A questionnaire was used to collect data which were then analysed descriptively by computing descriptive statistics and inferentially by multiple regression. The findings revealed that there was a positive relationship between politics, existing regulations and street vendors’ knowledge and the perception of street vendors regarding their legality. It is concluded that continuous contradictions in law creation and implementation contribute to more problems than solutions regarding street vending activities in urban settings. It is also concluded that politics and associated actions, existing regulations and their implementation, and street vendors’ knowledge positively influence street vendors’ perception regarding the legal status of street vending operations. It is recommended that urban authorities and politicians should set a plain ground on which operations of street vending activities will run.